METODS OF HOUSING CONTRUCTION STEPS IN PALANGKA RAYA CITY - Revianti Coenraad (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
Palangka Raya urban population growth is currently increasing, it impacts also the economy and the need for proper residence. This situation led to the increasing need for shelters that can be seen from the increasing filing of housing loans. This study will examine the application of housing development procedures in producing a housing product that will be transferred to consumers in a good quality product in the area of Palangka Raya. In the context of this study, development housing procedures is one of the quality systems that can be applied to residential construction project supply chain to produce a quality housing. A primary issue in this study is what is the description of procedures system on the housing development appropriate pattern and how can it be applied based on the conditions of existing resources in the City of Palangka Raya. Areas studied are middle-class residential population, in this case are consumers and housing developers in the city of Palangka Raya, who will be interviewed and filled out questionnaires that were made, and then drew the conclusion after obtaining the desired data. According to the results of the questionnaire, it can be concluded that the developers do not provide good service quality, while buyers of residential do not get the quality of housing they want. The results of this study is to get a quality house and fit in the city of Palangka Raya which made the stages as follows: identification of land ? material selec on ? land clearing ? soil heaping phase I ? bowplank installation ? founda on holing ? moun ng cerucuk Galam ? founda on assembling and casting ? founda3on sloof assembling and cas3ng ? soil heaping phase II ? adobe and sills installation. Based on construct validity results done by experts/specialists from the questionnaire that was analyzed, then obtained the validity of 88 that is in the category valid. This means that housing development procedures can be used as a standard concept of quality of housing construction type 36 which matches in Palangka Raya. Their housing development procedures is able to improve the quality of housing in the city of PalangkaRaya in this case the structure more robust and not easily cracked.